Micro-LED Array-Based Photo-Stimulation Devices for Optogenetics in Rat and Macaque Monkey Brains - Yasumi Ohta; Mark Christian Guinto; Takashi Tokuda; Mamiko Kawahara; Makito Haruta; Hironari Takehara; Hiroyuki Tashiro; Kiyotaka Sasagawa; Hirotaka Onoe; Reona Yamaguchi; Yoshinori Koshimizu; Kaoru Isa; et al. (IEEE Access, 2021)
Optogenetics is a powerful tool for controlling biological functions using light. Optical fibers have been extensively utilized in optical stimulation devices for optogenetics. However, the use of optical fibers results in a small photo-stimulation region. In this study, micro-LED array devices were developed to achieve large-area photo-stimulation in the brain of a large animal, such as macaque monkeys. Planar and linear micro-LED array devices were designed and fabricated to photo-stimulate the prefrontal cortex (PFC) and ventral tegmental area (VTA) of the brain and induce a neurochemical response. Device operation, optical intensity, and safety were first characterized using rats. Subsequently, the devices were used to photo-stimulate the brain of macaque monkeys. In addition, microdialysis in the PFC was performed. The devices detected modulated levels of dopamine in the brains. Thus, the photo-stimulation of both the PFC and VTA were successfully achieved, and the effectiveness of the developed micro-LED array devices was demonstrated. The study will help facilitate further studies on micro-LED array stimulation for system-wide optogenetic manipulation in large animals.